A novel ultrasound‐assisted vacuum drying technique for improving drying efficiency and physicochemical properties of Schisandra chinensis extract powder. Issue 1 (3rd November 2021) - Wang, Xuecheng; Xu, Shijun; Wu, Zhicheng; Li, Yuanhui; Wang, Yaqi; Wu, Zhenfeng; Zhu, Genhua; Yang, Ming
Abstract: Schisandra chinensis ( S. chinensis ) extract powder is an important intermediate for the preparation of many prepared medicines and health products. The physicochemical properties of S. chinensis extract powder have been found to vary tremendously and this has been attributed to the long drying time in the traditional drying method. In this study, S. chinensis specimens were authenticated as the dry fruit of S. chinensis (Turcz.) Baill. S. chinensis were extracted twice with 8 L kg −1 (liquid to solid ratio) distilled water. The extracts were mixed and concentrated under reduced pressure to 1.24 g cm −3 . Ultrasound‐assisted vacuum drying (UAVD) was employed as a new approach to improve the efficiency in drying S. chinensis extract powder and produce a higher quality product. The effects of drying temperature (70, 80, 90°C), ultrasonic power (40, 120, 200 W), and ultrasonic application time (4, 12, 20 min every 20 min) on the kinetics and quality of S. chinensis extract were investigated and compared with the conventional vacuum drying (CVD). It was shown that, with the increase in drying temperature, ultrasonic power, and time of UAVD, the drying time for S. chinensis extract to reach the equilibrium moisture decreased. The drying time was reduced by more than 25% when utilizing UAVD compared to the CVD method. The effective moisture diffusivity ( D eff ) values for CVD and UAVD were 3.48 × 10 –9 m 2 ·s –1 and 7.41 × 10 –9 m 2 s –1, respectively, at the drying temperature of 80°C, indicating an increase of 112.93%. It was also found that a Weibull distribution model was suitable for predicting the moisture content of S. chinensis extract ( R 2 > 0.95). Furthermore, the content of Schisandrol A in the extracts obtained from UAVD was 12.79% higher than that obtained using CVD at 90°C. This demonstrates that UAVD is an efficient drying technique for S. chinensis extract. Abstract : Ultrasonic enhancement on vacuum drying of Schisandra chinensis extract was studied. The kinetics of process and physicochemical properties were investigated. Ultrasound‐assisted vacuum drying improved the drying efficiency and product quality.